Transcriptome changes in grapevine (Vitis viniferaL.) cv. Malbec leaves induced by ultraviolet-B radiation - Pontin, Mariela Ana; Piccoli, Patricia Noemí; Francisco, Rita; Bottini, Ambrosio Rubén; Martinez-Zapater, José M.; Lijavetzky, Diego (2018)
Ultraviolet-B radiation (UV-B, 280-315 nm) is a natural component of sunlight, which has numerous regulatory effects on plant physiology. The nature of the response to UV-B is dependent on fluence rate, dose, duration and wavelength of the UV-B treatment. Some reports have analyzed the changes in gene expression caused by UV-B light on several plant species using microarray technology. However, there is no information on the transcriptome response triggered by UV-B in grapevine. In this paper we investigate the gene expression responses of leaves from in vitro cultured Vitis vinifera cv. Malbec plants subjected to the same dose of biologically effective UV-B radiation (4.75 kJ m-2 d-1) administered at two different fluence rates (16 h at ≅ 8.25 μW cm-2, 4 h at ≅ 33 μW cm-2) using a new custom made GrapeGen Affymetrix GeneChip®.